2000
DOI: 10.1177/0310057x0002800316
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Peripartum Meningitis

Abstract: A young primigravid parturient had an uneventful labour under epidural analgesia and delivered a healthy male infant. She returned 48 hours later with fever, vomiting and severe headache, but was misdiagnosed as having endometritis. Further signs of meningitis appeared six hours later, however she succumbed to the infection and died four weeks later despite intensive care and high-dose antibiotic management. Causes of meningitis in the peripartum period are discussed. The possibility of a causal association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Nevertheless, judging by the numbers of published cases, it could be the second commonest neurological complication of neuraxial analgesia in labour, after paraesthesiae. Loo et al 6 found 20 cases, 31,[43][44][45][46][47][48][49][50][51][52][53][54] while at least seven others [55][56][57][58][59][60][61] and one case of Herpes simplex encephalitis 62 among parturients, and dozens more among non-obstetric patients, have been reported since.…”
Section: Sources Of Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, judging by the numbers of published cases, it could be the second commonest neurological complication of neuraxial analgesia in labour, after paraesthesiae. Loo et al 6 found 20 cases, 31,[43][44][45][46][47][48][49][50][51][52][53][54] while at least seven others [55][56][57][58][59][60][61] and one case of Herpes simplex encephalitis 62 among parturients, and dozens more among non-obstetric patients, have been reported since.…”
Section: Sources Of Infectionmentioning
confidence: 99%
“…46 The outlook is generally good in the immunocompetent, although a death has been reported in an obstetric patient. 59 The causative organism, generally a viridans-type streptococcus of low virulence, lives harmlessly in the upper air passages and the vagina, but the cerebrospinal fluid provides it with a favourable culture medium. 13 In some cases, b-haemolytic Strep or Psuedomonas have been isolated, while in several instances no organisms have been grown, 31,44,51 and chemical contamination has been blamed.…”
Section: Sources Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Headache and neck pain or neck stiffness in a patient who recently had spinal anesthesia is often attributed to PDPH. One case report 34 highlighted the danger associated with missed diagnosis. Her condition deteriorated, and meningitis was not considered as a diagnosis until it was too late and the patient subsequently died in an intensive care unit.…”
Section: Infectious Complicationsmentioning
confidence: 99%